Efficacy of Dexmedetomidine Versus Midazolam in Preventing Etomidate Induced Myoclonus and Reduction of Hemodynamic Stress Response Following Intubation, A Multicenter Trial (Medical Forum Monthly, 2024)
Objective: The effectiveness of dexmedetomidine versus midazolam in preventing etomidate induced myoclonus and reduction of hemodynamic stress response following intubation.Study Design: A Randomized controlled trial.Place and Duration of Study: This study was conducted at the Department of Anesthesia at Multan Medical and dental College, Bakhtawar Amin Hospital, Ch Pervaiz Ellahi Institute cardiology, Multan and Sahiwal Medical College Sahiwal from January 2018 to March 2019.Materials and Methods: All 100 patients were indiscriminately allocated into two equal groups. Group-D was given dexmedetomidine and group-M was given midazolam. Age, weight, gender distribution, ASA status, hemodynamic factors (heart rate and mean blood pressure) and the incidence along with its severity were compared. Data was put in SPSS version 23 computer software and analyzed by applying Chi square and Independent t tests. P value ≤0.05 was considered of statistical importance.Results: Age, weight, gender distribution and ASA status was not significantly different between Group D and Group M (p >0.05). There was statistically noteworthy fall in post intubation heart rate as well as mean blood pressure in Group D as compared to Group M (p<0.05). Grade 0, 1, 2 and 3 myoclonus was seen in 56%, 30%, 16% and 2% patients of Group D; and 18%, 22%, 46% and 14% of the Group M patients, respectively (p <0.001).Conclusion: In the patients who premedicated with dexmedetomidine, the incidence as well as the intensity of myoclonus was considerably lower as compared to patients who were premedicated with midazolam. Moreover, dexmedetomidine was a successful agent to significantly attenuate the hemodynamic stress responses of intubation.